2019
DOI: 10.1088/1361-6382/ab10fb
|View full text |Cite
|
Sign up to set email alerts
|

One-loop quantum gravitational backreaction on the local Hubble rate

Abstract: We determine corrections to the Hubble rate due to graviton loops in a cosmological background spacetime of constant deceleration parameter. The corrections are gauge-invariant, based on a recent proposal for all-order gauge-invariant observables in perturbative quantum gravity. We find explicit expressions for the cases of matter-and radiation-dominated eras and slow-roll inflation with vanishing second slow-roll parameter. Interestingly, in the latter case the corrections can be described by a quantum-correc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(54 citation statements)
references
References 84 publications
2
51
1
Order By: Relevance
“…Our aim in this paper is to make use of the proposal of references [40][41][42] to compute the quantum-gravitational one-loop correction to a gauge-invariant observable measuring the space-time local expansion rate in slow-roll inflation, with both slow-roll parameters finite. Similar calculations were recently performed in de Sitter space-time [26] and in single-field inflation with constant deceleration parameter [27]. The calculation of Miao et al [26]h a s confirmed earlier expectations [18,19] that there is no quantum-gravitational backreaction on the expansion rate in de Sitter at one-loop order, although they leave the door open for effects at two-loop order.…”
Section: Introductionsupporting
confidence: 81%
See 4 more Smart Citations
“…Our aim in this paper is to make use of the proposal of references [40][41][42] to compute the quantum-gravitational one-loop correction to a gauge-invariant observable measuring the space-time local expansion rate in slow-roll inflation, with both slow-roll parameters finite. Similar calculations were recently performed in de Sitter space-time [26] and in single-field inflation with constant deceleration parameter [27]. The calculation of Miao et al [26]h a s confirmed earlier expectations [18,19] that there is no quantum-gravitational backreaction on the expansion rate in de Sitter at one-loop order, although they leave the door open for effects at two-loop order.…”
Section: Introductionsupporting
confidence: 81%
“…The condition on the scalar field perturbation also implies thatX (0) (2) = 0, as can be seen from equation (14), and this gauge choice simplifies equation (27)to 1) = H (1) , H (2) = H (2) .…”
Section: The Local Expansion Rate In Single-field Inflationmentioning
confidence: 99%
See 3 more Smart Citations